Educational policy : Vol. 1 no. 1 - Allington, Richard L.; Woodside-Jiron, Haley; National Research Center on English Learning and Achievement, Albany, NY. ([S.l.] : Distributed by ERIC Clearinghouse, 2004)
A study has been examining current directions in state education agency efforts to reform the elementary school language arts curriculum in four large, geographically diverse states with different policy mechanisms--California, New York, Wisconsin, and Texas. To understand policy development and implementation and discern how advocates advance a specific policy agenda, the agenda-setting process for educational policy is being examined using an approach developed by A. M. McGill-Franzen (1993) in her study of early childhood education literacy policies. Advocacy efforts targeted at implementing a more "code-oriented"--or phonics emphasis--curriculum framework have been observed in all of the states, but, to date, such efforts have been more successful in California and Texas than in New York and Wisconsin. The common advocacy tool observed was research supported by the National Institute of Child Health and Human Development (NICH) through the learning disabilities, cognitive, and social development program area. The agency chief and some NICH-supported researchers have been active in providing expert testimony to policy-making bodies and in disseminating their research results to national audiences. Most of their research has been with reading disabled or dyslexic children, and intervention designs have often focused on developing improved phonological awareness, pseudo-word decoding skills, word recognition, and text reading achievement in reading disabled children. How to interpret the research results has been a topic of debate--the question being whether research on more severely disabled readers informs as to the nature of the most appropriate curriculum emphasis in general education settings. The most quoted research document, the "30 years of research..." (Grossen, 1997) version contains seven instructional recommendations for classroom teachers. This analysis focuses on a critique of four of the seven recommendations. (Contains a table, 3 notes, and 38 references.) (NKA)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: R305A60005.
Microfiche.
Keywords: Agenda Setting